(untitled) (Journal of the College of Education for Women, 2019)
After a temporary halt to forced thghebr in different cities of Iraq this methodlogyopeations returned directiy in the areas of political conflict on the ground which are translatedoperations and forced displacement violence es they operations aimed at completing theforced displacement that occurred after the occupation in(2003)which took an upward curvepublicly after these events and some of which are aimed at the liquidation of some provincesthan any demographic diversity of religious or sectarian or alhens and others aimed atredemographic distribution within the province itself to produce a net sectarian zones as is thecase in Diyala Nineveh and Babylon Baghdad has the epicenter of sectarian violence and thenthey saw a quantum the largest of forced displacement due to the ferocity of the threats thatgoes on population whether due to direct the forced displacement or because of fear for theirlife or even the fear of arbitrary arrest.